Earth unbound: Climate change, activism and justice. Issue 14 (6th December 2021) - Lobo, Michele; Bedford, Laura; Bellingham, Robin Ann; Davies, Kim; Halafoff, Anna; Mayes, Eve; Sutton, Bronwyn; Walsh, Aileen Marwung; Stein, Sharon; Lucas, Chloe
Abstract: This experimental writing piece by the Earth Unbound Collective explores the ethical, political and pedagogical challenges in addressing climate change, activism and justice. The provocation Earth Unbound: the struggle to breathe and the creative thoughts that follow are inspired by the contagious energy of what Donna Haraway (2016 ) calls response-ability or the ability to respond. This energy ripples through monthly reading groups and workshops organised by this interdisciplinary collective that emerged organically in January 2020.